Ethics of Synthetic Life: A Jaina Perspective* - Key Chapple, Christopher (Worldviews, 2013)
Many Western philosophers, from Aristotle through Descartes and even Collingwood and Whitehead, have regarded the material world to be largely inert and subject to human intervention. The modern period has yielded more nuanced definitions of nature, seeing the process of life as self-generating and self-sustaining. The Jaina worldview, dating from the first several centuries before the common era, has developed an elaborate biological schematic that attributes sentience and hence soul to even the elements of earth, water, fire, and air. They also developed a sophisticated ethical response to the “livingness” of things. The Jaina attitudes toward synthetic life are explored at the end of the paper, suggesting that even engineered cells would nonetheless possess the qualities of life that must be valued and protected.